DINAMIKA KEPEMIMPINAN KEPALA DAERAH DI MASA TRANSISI: KAJIAN STRATEGIS ATAS TANTANGAN, ADAPTASI DAN KOLABORASI PEMERINTAHAN DAERAH - Made Wahyuni; Ketut Meri Puspita Sari (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2025)
This study examines the dynamics of regional head leadership during the transition period, a phase that often causes complexity in regional governance due to changes in political and administrative leadership. Leadership transitions can cause uncertainty in policy direction, declining bureaucratic performance and resistance within government organizations. Therefore, this study aims to understand the challenges faced by new regional heads, the adaptation strategies implemented and the collaboration patterns built with other stakeholders in maintaining government stability. The focus of the study lies in the strategic role of regional heads in bridging the internal dynamics of the bureaucracy and external expectations of the community amidst changes in leadership. The research method used is a qualitative approach with a case study strategy, which allows for in-depth exploration of the transition phenomenon in the regional government environment. Data were collected through in-depth interviews with regional heads, bureaucratic officials and community leaders, participant observation of government activities during the transition period and analysis of related policy and regulatory documents. Data analysis techniques were carried out thematically by grouping findings based on main themes such as structural and cultural challenges, communication and adaptation strategies and cross-sector collaboration models. Initial findings indicate that the success of regional heads during the transition period is largely determined by the ability to build open communication, carry out bureaucratic consolidation and form adaptive collaborative networks. The results of this study contribute to the development of transitional leadership theory and policy recommendations in strengthening sustainable and responsive regional governance.